Caring for hearts and minds: a quality improvement approach to individualized developmental care in the cardiac intensive care unit - Butler, Samantha C.; Rofeberg, Valerie; Smith-Parrish, Melissa; LaRonde, Meena; Vittner, Dorothy J.; Goldberg, Sarah; Bailey, Valerie; Weeks, Malika M.; McCowan, Sarah; Severtson, Katrina; Glowick, Kerri; Rachwal, Christine M. (Frontiers in Pediatrics, 2024)
Introduction: Infants with congenital heart disease (CHD) are at high risk for developmental differences which can be explained by the cumulative effect of medical complications along with sequelae related to the hospital and environmental challenges. The intervention of individualized developmental care (IDC) minimizes the mismatch between the fragile newborn brain's expectations and the experiences of stress and pain inherent in intensive care unit (ICU) environment.Methods: A multidisciplinary group of experts was assembled to implement quality improvement (QI) to increase the amount of IDC provided, using the Newborn Individualized Developmental Care and Assessment Program (NIDCAP), to newborn infants in the cardiac ICU. A Key Driver Diagram was created, PDSA cycles were implemented, baseline and ongoing measurements of IDC were collected, and interventions were provided. Results: We collected 357 NIDCAP audits of bedside IDC. Improvement over time was noted in the amount of IDC including use of appropriate lighting, sound management, and developmentally supportive infant bedding and clothing, as well as in promoting self-regulation, therapeutic positioning, and caregiving facilitation. The area of family participation and holding of infants in the CICU was the hardest to support change over time, especially with the most ill infants. Infants with increased medical complexity were less likely to receive IDC. Discussion: This multidisciplinary, evidence-based QI intervention demonstrated that the implementation of IDC in the NIDCAP model improved over time using bedside auditing of IDC.